2011
DOI: 10.1194/jlr.m011080
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin increases intestinal expression of NPC1L1 in hyperlipidemic men

Abstract: The relationship between elevated plasma levels of LDLcholesterol (LDL-C) and the risk of atherosclerosis has been very well established ( 1-3 ). Clinical trials have shown that reduction of LDL-C constitutes a primary strategy for the prevention and regression of coronary heart disease ( 4 ). Plasma cholesterol levels are regulated by feedback mechanisms including exogenous cholesterol absorption through the gastrointestinal tract and endogenous cholesterol synthesis by various tissues. Several studies have s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(70 citation statements)
references
References 53 publications
(34 reference statements)
3
63
1
1
Order By: Relevance
“…This, however, does not negate the published fi ndings of glucagon on the Srebp-2 pathway, including LDLR ( 46 ), PCSK9 ( 50 ), and cholesterol synthesis ( 29 ). The induction of GRA on GLP-2 is so dramatic that it might have masked the activation on the Srebp-2 pathway caused by blockade of GCGR, inasmuch as intestinal cholesterol absorption and hepatic cholesterol synthesis are reversely affected by each other ( 51,52 ). Another set of observations obtained in the present studies of GRA treatment that we posit to be fruitful for further examinations concerns bile acids.…”
Section: Discussioncontrasting
confidence: 43%
“…This, however, does not negate the published fi ndings of glucagon on the Srebp-2 pathway, including LDLR ( 46 ), PCSK9 ( 50 ), and cholesterol synthesis ( 29 ). The induction of GRA on GLP-2 is so dramatic that it might have masked the activation on the Srebp-2 pathway caused by blockade of GCGR, inasmuch as intestinal cholesterol absorption and hepatic cholesterol synthesis are reversely affected by each other ( 51,52 ). Another set of observations obtained in the present studies of GRA treatment that we posit to be fruitful for further examinations concerns bile acids.…”
Section: Discussioncontrasting
confidence: 43%
“…This alteration in apoB-48 metabolism may be another mechanism by which CETP inhibition contributes to the reduction of CHD risk in humans. of ABCG5 and ABCG8, without changing signifi cantly the expression of apoB-48 ( 44 ). There is, however, a great deal of individual variability in these studies, and the precise effect that statin therapy has on apoB-48 metabolism may depend on the underlying lipoprotein disorder.…”
Section: Discussionmentioning
confidence: 80%
“…Ezetimibe potentiates the effect of statins, increasing their effectiveness by another 15 -20% in relation to cholesterol lowering. Trembly et al [69] this year reported an increase in NPC1L1 by 19% in the small intestine in subjects on atorvastatin thus describing a mechanism whereby cholesterol absorption is increased in patients on statins. In animal studies we have demonstrated an increase in cholesterol absorption in diabetes [70] We asked the question as to whether diabetes might be associated with an increase in cholesterol absorption through stimulation of NPC1-L1.…”
Section: The Chylomicron In Diabetesmentioning
confidence: 99%